USULAN PENERAPAN MANUFACTURING RESOURCE PLANNING (MRP II) DI PT KSP - Hayun, Anggara; Johanda, Johanda (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
PT KSP is a fibrous food product manufacturing companies "Nata De Cocoâ. MostÂ common problems that arise are shortages or overstocking of products. The purpose of this study isÂ to propose the implementation of Manufacturing Resource Planning system (MRP II). Data isÂ obtained by using forecasting, aggregate planning, capacity requirements planning resourcesÂ (Resource Requirement Planning), master production scheduling (MPS), MPS validationÂ (Rough Cut Capacity Planning), and Bill of Material to Material Requirement PlanningÂ (MPR). Forecasting data are taken from best forecasting results with Linear RegressionÂ forecasting method. Aggregate planning is conducted after forecast with least cost analysis, namelyÂ the chase method which can be continuously used to MRP. Best forecasting results with theÂ smallest error will be taken from the forecast of the next 3 periods for base calculation ofÂ materials. This study concluded that the company can apply MRP II, to ensure steady flow ofÂ production and in the process also better in meeting consumer demand.